2020
DOI: 10.4018/ijsssp.2020010102
|View full text |Cite
|
Sign up to set email alerts
|

Factors in Information Assurance Professionals' Intentions to Adhere to Information Security Policies

Abstract: Information security policies (ISPs) serve to clarify and formalize organizational information security practices and reduce data risks, but research shows that ISP noncompliance remains a prominent concern for both scholars and practitioners. This study utilized the unified theory of acceptance and use of technology 2 (UTAUT2) to explore factors that predict information assurance professionals' behavioral intentions to comply with ISPs. The research question addressed: To what extent do performance expectancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Performance expectancy refers to the belief that the use of technology in certain situations can be beneficial as it improves performance (Venkatesh et al 2012). Studies with UTAUT as the theoretical framework have always shown that there is a statistically significant relationship between expected performance and user acceptance of the technology's behavioral intent (Engotoit, Kituyi, and Moya 2016;S. Raschid Muller and Mary L. Lind 2020).…”
Section: Performance Expectancymentioning
confidence: 99%
See 2 more Smart Citations
“…Performance expectancy refers to the belief that the use of technology in certain situations can be beneficial as it improves performance (Venkatesh et al 2012). Studies with UTAUT as the theoretical framework have always shown that there is a statistically significant relationship between expected performance and user acceptance of the technology's behavioral intent (Engotoit, Kituyi, and Moya 2016;S. Raschid Muller and Mary L. Lind 2020).…”
Section: Performance Expectancymentioning
confidence: 99%
“…Due to the limitations and bias in the previous studies related to technology adoption and security compliance, the results are very weak and difficult to digest. For example, the (Muller & Lind, 2020) suggested that UTAUT2 may not be a good model for examining ISP compliance amongst security professionals. This may not be the case with general public and all employees of the organizations because information assurance professionals usually have more knowledge and bias towards compliance.…”
Section: Proposed Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the use of the UTAUT2 in the present study addressed a gap in the research literature and contributed to knowledge about end-users' behavioral intentions to comply with ISPs [31].…”
Section: Utaut2 and Behaviormentioning
confidence: 94%
“…A statistical survey is one of the earliest technologies used in intrusion detection technology, and many commercial versions of intrusion detection products still use this technology [19].…”
Section: Information Security Assurance Algorithms and Privacy Protec...mentioning
confidence: 99%